2006
DOI: 10.4269/ajtmh.2006.74.205
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Distribution of Antimalarial Drug-Resistant Alleles Among Isolates of Plasmodium Falciparum in Bangui, Central African Republic

Abstract: We determined the baseline frequency distribution of mutant alleles of genes associated with resistance to chloroquine and sulfadoxine-pyrimethamine in Plasmodium falciparum isolates in Bangui, Central African Republic. Mutant alleles of the P. falciparum chloroquine resistance transporter (pfcrt) gene were found in all samples and the frequency of the deduced CIET pfcrt haplotype was high (45%). The most common allele of the P. falciparum multidrug resistance 1 (pfmdr1) gene among the field isolates of P. fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Recently, this mutation has been found in Malawi, in parasites from human immunodeficiency virus-positive pregnant women, by using a real-time PCR method and a heteroduplex tracking assay (1, 26); however, this has not been confirmed in a subsequent study in the same area (42). This Ile-164-Leu mutation has also been reported in Uganda and the Central African Republic (16,35,51), and a recent study showed prevalences of 4 to 14% at two sites in Uganda where P. falciparum is endemic (31). Interestingly, this mutation has been found in the western part of Kenya by using standard PCR methods and cloning; surprisingly, its presence was not associated with reduced PM-SD efficacy (21,34), questioning its clinical relevance.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, this mutation has been found in Malawi, in parasites from human immunodeficiency virus-positive pregnant women, by using a real-time PCR method and a heteroduplex tracking assay (1, 26); however, this has not been confirmed in a subsequent study in the same area (42). This Ile-164-Leu mutation has also been reported in Uganda and the Central African Republic (16,35,51), and a recent study showed prevalences of 4 to 14% at two sites in Uganda where P. falciparum is endemic (31). Interestingly, this mutation has been found in the western part of Kenya by using standard PCR methods and cloning; surprisingly, its presence was not associated with reduced PM-SD efficacy (21,34), questioning its clinical relevance.…”
Section: Discussionmentioning
confidence: 89%
“…Of relevance, the only other place in Africa where a high frequency on May 10, 2018 by guest http://aac.asm.org/ (14%) of the genotype with a polymorphism at position 164 in pfdhfr has been reported is Kabale in Uganda (16), which is close to the eastern Rwanda border. The genotype with a polymorphism at position 164 in pfdhfr has been reported at lower frequencies in Kenya (18), Malawi (1), and Central Africa (19) and from travelers returning from Ghana and Kenya (9). The quadruple mutant is prevalent at higher frequencies in Southeast Asia and South America, where SP is no longer effective.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, in addition to the conventional in vivo and in vitro methods, the molecular markersbased approach to study and elucidate antimalarial drug resistance has proved useful [22][23][24][25][26]29,30,32]. In this study, we described the distribution of pfcrt K76T and pfmdr1 N86Y mutations in the study area and attempted to evaluate the correlation of these mutations with in vivo clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%